Forensic toxicology drug use and misuse - Davies, Susannah; Johnston, Atholl; Holt, David W. (Royal Society of Chemistry, 2016)
The text begins with an in-depth discussion of pharmaco-epidemiology, including information on the value of nationwide databases in forensic toxicology. The use and abuse of drugs in driving, sport and the workplace are then discussed by industry experts who are conducting case work in their fields. Not only are new drug groups discussed (NPS), but also their constantly changing impact on drug legislation. Synthetic cannabinoids, khat and mephodrone are discussed in detail. Following a section devoted to legislation and defence, readers will find comprehensive chapters covering sample choice reflecting the increasing use of hair and oral fluid, also the less commonly used sweat and nail analysis. New and old case examples are compared and contrasted in the final part of the book, which will enable readers to understand how drugs impact on each other and how the interpretative outcome of a case are dependent on many aspects.